2004
DOI: 10.1042/cs20030412
|View full text |Cite
|
Sign up to set email alerts
|

Diminished L-arginine bioavailability in hypertension

Abstract: L-Arginine is the precursor of NO (nitric oxide), a key endogenous mediator involved in endothelium-dependent vascular relaxation and platelet function. Although the concentration of intracellular L-arginine is well above the Km for NO synthesis, in many cells and pathological conditions the transport of L-arginine is essential for NO production (L-arginine paradox). The present study was designed to investigate the modulation of L-arginine/NO pathway in systemic arterial hypertension. Transport of L-arginine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
0
8

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 38 publications
6
66
0
8
Order By: Relevance
“…An association between L-arginine and hypertension has been suggested in 2 smaller previous studies. 39,40 This apparently paradoxical association may be attributable to abnormalities in L-arginine transport via system yϩ, which may limit intracellular availability or L-arginine for NO synthesis. 39,40 This transport system has been shown to be abnormal in hypertension.…”
Section: Large Artery Stiffness Hypertension and Arterial Hemodynamicsmentioning
confidence: 99%
“…An association between L-arginine and hypertension has been suggested in 2 smaller previous studies. 39,40 This apparently paradoxical association may be attributable to abnormalities in L-arginine transport via system yϩ, which may limit intracellular availability or L-arginine for NO synthesis. 39,40 This transport system has been shown to be abnormal in hypertension.…”
Section: Large Artery Stiffness Hypertension and Arterial Hemodynamicsmentioning
confidence: 99%
“…This is of particular interest as it remains to be determined why only a subset of subjects with obesity subsequently develop hypertension. 62 In this context, it is of interest that even normal weight subjects with essential hypertension have reduced l-arginine transport and NO bioavailability, 63 indicating that impaired l-arginine-NO pathway is associated with hypertension regardless of the underlying cause. Furthermore, a functionally relevant genetic polymorphism relating to l-arginine transport is present in human essential hypertension.…”
Section: Are No Bioavailability and L-argininementioning
confidence: 99%
“…62 En este contexto, es interesante destacar que incluso sujetos con peso normal e hipertensión esencial presentaron disminución del transporte de L-arginina y de la disponibilidad de NO, 63 lo que indica que la alteración en la vía L-arginina-NO se relaciona con la hipertensión independientemente de la causa subyacente. Además, un polimorfismo gené-tico funcionalmente relevante relacionado con el transporte de L-arginina se encuentra presente en la hipertensión esencial en humanos.…”
unclassified
“…Although the results support our hypothesis, it is necessary to determine whether L-arginine supplementation in chicks indeed increases NO and/or cGMP production in the aortic wall. It has been reported that the uptake of L-arginine into platelets from hypertensive humans and the transport of L-arginine into red blood cells of hypertensive rats are lower than those in normotensive controls (27); L-citrulline production was also reduced in platelets from hypertensive humans (25). In contrast, L-arginine treatment increased the NO content of ischemic myocardium and reduced apoptosis of myocytes (21).…”
Section: Discussionmentioning
confidence: 99%